Untapping the Determinants of Islamic Financial Behaviour among Young Generations - Ishak, Muhammad Arif Fadilah; Muhammad Zuki, Mohd Faizuddin; Hassan, Muhammad Hafiz (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research originality: The originality of this research lies in its integrated examination of psychological, social, and educational determinants of Islamic financial behaviour within a localized Malaysian context. Research objectives: Grounded in the Theory of Planned Behaviour, the research investigates how Islamic financial literacy, financial risk attitude, parental financial socialization, and financial self-efficacy influence financial behaviour. Research methods: A structured questionnaire was distributed to 358 respondents aged 18 to 30, and the data were analyzed using covariance-based Structural Equation Modelling (CB-SEM). Empirical result: The study reveals two significant findings: parental financial socialization and financial self-efficacy strongly predict Islamic financial behaviour, while financial literacy and risk attitude show insignificant relationships. Implications: Policymakers should embed Islamic financial literacy in national youth programs, educators must integrate hands-on financial training into curricula, and Islamic finance providers are encouraged to offer youth-friendly, Shariah-compliant products supported by educational outreach and family-involved financial awareness initiatives. JEL Classification: D10, D14, D91, G41